(untitled) (International Journal of Biomedical and Advance Research, 2016)
Herbal medicine is the oldest form of healthcare known to the human race with a history of documentation for almost 4000 years. The Mikania glomerata Sprengel, popularly known as ’guaco’, have a long standing record of application for the treatment of certain common ailments and at times of alarming emergency circumstances. In this study, Mikania glomerata was collected and processed against anticancer purposes. The aqueous extract of Mikania glomerata was challenged against H292 human lung cancer cell for anticancer activity. The results of cytotoxicity study using MTT assay on H292 human lung cancer cells in the presence of aqueous extract of Mikania glomerata proved that the plant extract inactivated the cancer cells . Exposure of cultures to the extract for 24hr in the concentrations 10 g/ml, 20 g/ml, 30 g/ml and 40 g/ml had a mean OD of 0.83 0.06, 0.893 0.09, 0.816 0.1 and 0.861 0.05 correspondingly indicating no cytotoxicity in all the tested doses. Hence, this study confirmed that this plant may act as an alternative anticancer agent in near future.